The Effects of Seasonal Changes on Biochemical Changes of some Citrus Species - Arabzadeh, Esmat; Ghazviny, Reza Fotuhi; Zakizadeh, Hedayat; Eshghy, Saeed; Saadatian, Mohammad (Asian Journal of Biological and Life Sciences)
Seasonal changes cause an array of physiological, biochemical and morphological changes in plants, thereby affecting plant growth and development. The measurement of some biochemical indexes is a method for the evaluation of cultivars, and the explanation of their behavioral patterns from normal to severe environmental changes. This study was carried out to investigate the effects of seasonal changes on the changes of antioxidant capacity, total protein, peroxidase (POD) and superoxide dismutase (SOD) in five citrus species (the Valencia orange, Kinow tangerine, Mexican lime, Persian lime and Darab native orange) during the four seasons of the year with three replications in the statistical design split plot. The leaves of these species were sampled in May, August, November and February in the range of the average temperatures 21-25, 31-35, 15-20 and 10-15°C, respectively. Results show that amount of protein, total antioxidant capacity and POD in the spring (the time of fruit growth and development) was great. The comparison between the data averages demonstrated that the protein and the POD enzyme have the minimum activity in the summer, whereas the SOD had the maximum activity in the summer (as the hottest season of the year). The amount of POD enzyme in Persian lime and Mexican lime was considerably greater than that of the other investigated cultivars. These two cultivars can be a source of producing the commercial POD. The greatest amount of protein was observed for the Darab native orange and Persian lime and the smallest amount was observed in the Valencia orange in the summer.
Keywords: Antioxidant enzyme; Citrus; Environment; Stress; Superoxide dismutase